Geothermal Reservoir Identification based on Gravity Data Analysis in Rajabasa Area- Lampung - Muh Sarkowi; Rahmat Catur Wibowo (Indonesian Institute of Sciences, 2021)
Gravity research in the Rajabasa geothermal prospect area was conducted to determine geothermalreservoirs and faults as reservoir boundaries. The research includes spectrum analysis and separation of the Bouguer anomaly to obtain a residual Bouguer anomaly, gradient analysis using the second vertical derivative (SVD) technique to identify fault structures or lithological contact, and 3D inversion modeling of the residual Bouguer anomaly to obtain a 3D density distribution subsurface model. Analysis was performed based on all results with supplementary data from geology, geochemistry, micro-earthquake (MEQ) epicenter distribution map, and magnetotelluric (MT) inversion profiles. The study found 3 (three) geothermal reservoirs in Mount Balirang, west of Mount Rajabasa, and south of Pangkul Hot Spring, with a depth of around 1,000-1,500 m from the ground level. Fault structures and lithologies separate the three reservoirs. The location of the reservoir in the Balirang mountain area corresponds to the model data from MEQ, temperature, and magnetotelluric resistivity data. The heat source of the geothermal system is under Mount Rajabasa, which is indicated by the presence of high-density values (might be frozen residual magma), high-temperature values, and the high number of micro-earthquakes epicenters below the peak of Mount Rajabasa.